KALIKHA empowering the Filipino animation industry through an animation incubator - Umipig, Seth Ephraim G. (College of Architecture, University of the Philippines Diliman, 2025)
The Filipino animation industry has been producing high quality animated media for over four decades. Despite all its talent however, it is heavily reliant on outsourced projects from foreign studios, hindering the development of original Filipino animated media. Local studios are therefore designed to maximize the mechanized production, required by these outside studios, limiting the creative work of artists. By focusing on the intersection of architecture and animation, this study explores how the design of an animation studio incubator can empower local studios to transition from mechanized animation production to creative processes. Set within the context of Quezon City's Knowledge-Business District, this project capitalizes on its proximity to media hubs and adjacent creative industries, offering a strategic location for an animation incubator. Using a mixed-method approach, the research integrates descriptive studies to identify spatial requirements for animation studios and phenomenological studies to understand the creative processes of animators. Findings of the study are applied in the architectural design through several approaches such as creative placemaking and spatial sequencing, all aimed at creating a dynamic and adaptive environment for animators. Preliminary findings highlight the need for creative spaces: rooms for personal work, stations for collaborative meetings, areas for presentation and making spaces. The animation incubator seeks to bridge gaps in the industry by incubating ideas, enhancing creativity, and providing a platform for Filipino animators to produce globally competitive content. This undertaking not only contributes to the architecture field by exploring its intersection with animation but also supports the national agenda of transitioning to a knowledge-based economy, highlighting architecture's potential to influence economic and cultural growth.